Towards Improving the Academic Bodies of FIME in the Autonomous University of Nuevo León, México - María Isabel Dimas-Rangel; Arturo Torres-Bugdud; Jaime Arturo Castillo-Elizondo (Universidad Nacional, Costa Rica, 2012)
This paper refers to a crucial issue for higher education institutions.  In Mexico, particularly, the collective work of academic bodies is an unresolved issue despite the efforts made in this regard. In this context, a well-founded systematic discussion is essential to understand the potential of these academic bodies on faculty strengthening and their subsequent impact on the quality of education. This paper presents the results of a research project conducted by FIME  with the purpose of identifying the characteristics of its academic bodies as well as their current and potential condition.   (1) Translator's Note: FIME refers to the Facultad de Ingeniería Mecánica y Eléctrica (College of Mechanical and Electrical Engineering).